Application of the Problem-Based Learning Model to Improve Students' Understanding of Welding Defect Material - Yayan Srinatriyo; Suhartadi, Syarif; Yoto (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
The purpose of the study is to observe the Problem-Based Learning learning model; it is hoped that students, as prospective welding welders, can understand the types and forms of welding defects that arise to assess the quality of welding performed. This research was conducted on grade XI Las 2 students of SMKN 1 Udanawu using the classroom action research method (Classroom Action Research). The results of the research conducted obtained an increase in the average completeness results of students from the precycle, cycle I, and cycle II students of grade XI Las 2 SMKN 1 Udanawu, which initially only reached 30.2 in the precycle to 56.4 in cycle I and in cycle II to 81.3. This happens because, in practice-based learning, students only concentrate on practice and ignore theories related to welding defects. After Problem-Based Learning is carried out, students better understand the causes and effects of welding defects that arise. The factor that increases student understanding in cycles I and II is that learning is made in groups, so students are more active in identifying welding defects. In cycle II, students present the identification results so that students indirectly understand the material related to welding defects. From the increased learning outcomes, students can judge the welding quality performed.